AN ANALYSIS OF STUDENTS’ ERRORS IN SOLVING SOCIAL ARITHMETIC WORD PROBLEMS USING NEWMAN’S ERROR ANALYSIS - Hafizhah Khairunnisa; Hayatun Nufus (Prodi. Pendidikan Matematika, FKIP, Universitas Riau, 2025)
This study aimed to analyze students’ errors based on Newman’s Error Analysis in solving mathematical word problems on social arithmetic material. The type of research used was qualitative research with a descriptive method. The subjects were selected using purposive sampling, with 9 students of Class VII A at UPT SMPN 7 Tambang chosen from 32 students based on different achievement levels. The instruments used in this study included mathematics test items on social arithmetic material, interview guidelines, and documentation. All data were analyzed through the stages of data reduction, data display, and conclusion drawing. The results of the study showed that: (1) students with high achievement generally made transformation errors, namely being incomplete in writing mathematical models; process skill errors, namely using the correct process, but obtaining incorrect answers; and encoding errors, namely making mistakes in drawing conclusions and not writing the final conclusion. (2) Students with average achievement generally made transformation errors, namely being incomplete in writing mathematical models and making mistakes in writing mathematical models; process skill errors, namely using the wrong process so that the answers were incorrect, being unable to solve the problems, and using the correct process, but still obtaining incorrect answers; as well as encoding errors, namely making mistakes in drawing conclusions and not writing the final conclusion. (3) Students with low achievement generally made transformation errors, process skill errors, and encoding errors because they did not answer the problems and were unable to solve the problems.